Evaluation Of Bni Credit Granting System and Procedure Flexion at PT. Bank Negara Indonesia (PERSERO) Tbk Fatmawati Branch Office South Jakarta - Rysma Diah Hendrasty; Devid Putra Arda; Hendra Candra (International Forum of Researchers and Lecturers, 2025)
BNI Fleksi Credit is a KTA facility offered to employees with fixed income for consumption purposes. The procedure for granting BNI Fleksi credit by Bank BNI Branch. Fatmawati still has problems, one of which is not providing physical collateral and there are still prospective debtors who do not understand the terms and conditions in applying for BNI Fleksi credit facilities. The purpose of this study is to find out what are the terms and conditions in applying for BNI Fleksi credit, to find out how the implementation of BNI Fleksi credit provision, to understand the various obstacles in the process of granting BNI Fleksi credit by Bank BNI Fatmawati Branch. The study method used is descriptive qualitative method. The result of the study shows that, 1) BNI Fleksi credit that has been implemented runs quite well and has been in accordance with the procedures and provisions, however, there are still some obstacles faced, one of which is the completeness of document requirements as support in the process of granting BNI Fleksi credit has not met the requirements. 2) In BI Checking, there are still prospective debtors who have arrears at various banks. 3) BNI Flexi Credit customers experience delays in paying principal and interest installments due to the company being late in paying salaries to employees, this has an impact on installment payments and the occurrence of collectibility which is the possibility of not receiving back the loan that has been given. 4) Refusal to provide BNI Flexion to prospective debtors because they do not guarantee themselves with credit insurance that can protect the risk of inability to pay, death, bankruptcy, termination of employment, repayment of remaining credit interest and arrears, and also simplify the loan application process.